Upfront pancreaticoduodenectomy in severely jaundiced patients: is it safe?. (17th October 2019) - Pamecha, Viniyendra; Sadashiv Patil, Nilesh; Kumar, Senthil; Rajendran, Vivek; Gupta, Sahil; Vasantrao Sasturkar, Shridhar; Kumar Sinha, Piyush; Arora, Asit; Agarwal, Nikhil; Baghmar, Saphalta
Abstract: Aim: The aim of this study was to evaluate the outcomes following upfront pancreaticoduodenectomy (PD) in severely jaundiced (serum bilirubin level ≥15 mg/dl) patients with malignant distal common bile duct (CBD) obstruction. Background: Recent studies have failed to show the benefits of preoperative biliary drainage (PBD) before PD. In addition, there is limited data on the impact of upfront PD on perioperative outcomes in severely jaundiced patients. Methods: We reviewed the prospectively collected data of 177 patients who had undergone PD for the malignant distal CBD obstruction from May 2009 to May 2018. Study subjects were divided into Group A (severely jaundiced patients with upfront PD; n  = 20), Group B (patients with serum bilirubin <15 mg/dl and no PBD; n  = 88) and Group C (PBD prior to PD; n  = 69). Overall morbidity, in‐hospital mortality, and postoperative hospital stay were compared. Results: No significant differences were noted between the three groups regarding sex, tumor size and stage, comorbidities, and surgical technique. The intra‐operative blood loss was more in severely jaundiced patients as compared to Groups B and C (605 vs. 300 vs. 350 ml, P  = 0.0001), but similar operative times, blood transfusions, and rates of post‐pancreatectomy leak and hemorrhage. The infective complications were significantly less with upfront surgery. The overall morbidity, in‐hospital mortality, and hospital stay were comparable between the three groups. Multiple logistic regression analysis failed to identify both the presence of preoperative jaundice and hyperbilirubinemia ≥15 mg/dl as independent risk factors for post‐PD major morbidity. Conclusion: Upfront PD can be performed safely in the selected severely jaundiced patients and is associated with significantly lower infective complications. Abstract : Highlight To evaluate the propriety of preoperative biliary drainage, Pamecha and colleagues compared the outcomes of upfront pancreaticoduodenectomy in severely jaundiced patients with those of surgery after biliary drainage. They concluded that upfront pancreaticoduodenectomy can be performed safely in selected severely jaundiced patients and is associated with significantly lower infective complications.